A killer's mind - Omer, Mike (Zoe Bentley mystery, 2018)
"Thoughts of the killer still roaming free in the streets chilled Zoe's heart, but it fascinated her to[o]... She took out the scrapbook from under the bed and opened it to the next free page. Then she carefully cut the article from the paper. She leaned her back against the door, prepared to shove the paper and scrapbook under the bed if her parents suddenly barged in. She taped the article into the scrapbook and read it again. Progress. What could that mean? Were they about to arrest the killer? The man who grabbed women at night, stripping them and killing them? The monster? That was the papers favorite word when mentioning the killer. A monster on the loose. A monster preying on helpless women. A monster hiding in Maynard. But Zoe realized the horrifying truth. This wasn't a monster. This wasn't some sort of alien or a scaly creature rising from the sewers. Much worse. It was a man."